Professionalität und Postkonventionalität. Entwicklungstheoretische und soziologische Perspektiven auf professionalisiertes Handeln - Zizek, Boris (ETHICS IN PROGRESS, 2014)
The purpose of the following article is to point out the essential role of postconventional moral judgement in professionalized action. By some examples I will demonstrate that it is the precondition of completed professionalization.